A simple way to induce anode-electrolyte interface engineering through a functional composite separator for zinc–nickel batteries. (15th June 2022) - Zhao, Zequan; Wang, Chunying; Wang, Haozhi; Shen, Yuanhao; Wang, Qingyu; Li, Siwen; Liu, Bin; Zhao, Naiqin; Zhong, Cheng; Hu, Wenbin
Abstract: Along with the developments of large-scale energy storage system, Zn–Ni battery has received much attention. However, the poor cycling life and shelf life of Zn–Ni battery strongly limit its practical application. Herein, a solid-state functionalized composite (FC) separator was developed through a simple strategy to steadily regulate the anode-electrolyte interface characteristics to comprehensively improve the performance of Zn–Ni battery. FC separator has interaction with anode to guide even Zn deposition during cycling. As a result, the battery assembled with FC separator achieves superb cycling life of 1435 h (848 th cycle). In addition, under the function of the PAAK from FC separator, hydrogen evolution reaction can be mitigated. The water retention ability has also been improved to ensure good storage performance, in which the battery exhibits an open circuit voltage higher than 1.63 V after 618 h at a high temperature of 60 °C. Besides, the negative effect brought by oxygen from cathodes has been reduced. Consequently, the battery keeps a high discharge capacity without breakdown for more than 800 h floating charge at 60 °C. The results demonstrate the large potentials for use in next-generation Zn–Ni batteries. Graphical Abstract: ga1 Highlights: A stable interface engineering is realized through a novel functional separator. The separator exhibits stronger attraction to Zn to guide its deposition behavior. The separator and the modified anode interface mitigate the side reactions. The water retention ability is enhanced for long-term storage. Zn–Ni battery has an impressive long cycling life and achieves significantly improved shelf life under 60℃.